2019
DOI: 10.1088/1361-648x/ab482b
|View full text |Cite
|
Sign up to set email alerts
|

Chemically modified phosphorene as efficient catalyst for hydrogen evolution reaction

Abstract: Hydrogen gas produced by electrolysis has been considered as an excellent alternative to fossil fuels. Developing non-noble metal catalysts with high electrocatalytic activities is an effective way to reduce the cost of hydrogen production. Recently, black phosphorus (BP) based materials have been reported to have good potential as electrocatalysts for hydrogen evolution reaction (HER). Herein, we systematically study the catalytic performance of monolayer BP (phosphorene) and several chemically modified phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Feng et al uncovered that the armchair edge exhibited much better catalytic activity than the plane sites and zigzag edges by means of DFT calculations (Figure 4b). [96] Nevertheless, phosphorene suffers from chemical degradation under water-and oxygen-containing conditions, causing a major obstacle to produce phosphorene from bulk BP by liquid exfoliation. Therefore, to keep BP away from chemical degradation, some surface modification routes, including coupling with organic or inorganic ligands, as well as encapsulating carbon layer on the surface of BP, have been developed.…”
Section: Phosphorenementioning
confidence: 99%
See 2 more Smart Citations
“…Feng et al uncovered that the armchair edge exhibited much better catalytic activity than the plane sites and zigzag edges by means of DFT calculations (Figure 4b). [96] Nevertheless, phosphorene suffers from chemical degradation under water-and oxygen-containing conditions, causing a major obstacle to produce phosphorene from bulk BP by liquid exfoliation. Therefore, to keep BP away from chemical degradation, some surface modification routes, including coupling with organic or inorganic ligands, as well as encapsulating carbon layer on the surface of BP, have been developed.…”
Section: Phosphorenementioning
confidence: 99%
“…Reproduced with permission. [96] Copyright 2019, IOP. c) LSVs for HER of bulk BP, milled BP, NH 2 -BP nanosheets, GC and Pt at 5 mV s −1 in 1 m KOH.…”
Section: Borophenementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, chemical modified BP by surface adsorbing NH 2 /OH functional groups and doping N/S/C/O atoms into the lattice also have been demonstrated based on the first‐principles simulations. Theoretical calculations showed that both heteroatoms doping and functional groups introducing could effectively enhance the HER catalytic performance of the plane and zigzag edge of BP, but degrade the catalytic activity of armchair edge slightly . A very recently research via DFT calculations reported that the HER activity of BP originated from defects and the reaction could be activated by atomic vacancies and edges based on the quantitative evaluation of the Gibbs free energy of the ad/desorption of hydrogen (H*) to/from phosphorene (ΔG H* ) .…”
Section: Bp Based Electrocatalysts For Hermentioning
confidence: 99%
“…Despite this fact, the interest in phosphorene remains enormous because of its semiconductor properties and anisotropic structural features . Furthermore, strong intralayer bonding, weak van der Waals interlayer interaction, tunable band gaps, high charge transport, and optical response properties, as well as chemical reactivity, make phosphorene an appropriate candidate for optoelectronics, energy storage, , sensing, and catalysis. , …”
Section: Introductionmentioning
confidence: 99%